THE USE OF LEARNING MEDIA ON LISTENING SKILL IN TEACHING INDONESIAN TO SPEAKERS OF OTHER LANGUAGE (TISOL) - Loren, Fabio Testy Ariance (English Department FBS UNP, 2017)
Listening skill is a language skill that has a very important role as the beginning of other skills. teaching Indonesian to speakers of other language learners in Integrated Language Service Unit Universitas Sebelas Maret have difficulty in listening skills due to the limited learning tools. This study aims to describe the use of learning media in listening skills in teaching Indonesian to speakers of other language (TISOL) at Integrated Language Service Unit Universitas Sebelas Maret. This research is a descriptive qualitative research with case study research strategy. Sampling technique used purposive sampling. Sources of data in this study were informants, events, books, scientific journal articles, student assignment results and relevant studies. Technique of collecting data in this research is observation, interview, and document analysis. Validity of data in this research was conducted by triangulation method and source. Research data were analyzed using interactive analysis model. The results showed that the use of learning media listening skills in teaching Indonesian to speakers of other language at Integrated Language Service Unit Universitas Sebelas Maret was done with two patterns, namely the use of media inside and outside the classroom. Learning media outside the classroom is further divided into individual learning media, group learning media, and mass media learning.Â Keywords: TISOL, learning media, listening skillPEMAKAIAN MEDIA PEMBELAJARAN KETERAMPILAN MENYIMAK DALAM PEMBELAJARAN BAHASA INDONESIA BAGI PENUTUR ASING Â AbstrakKeterampilan menyimak merupakan keterampilan berbahasa yang memiliki peranan sangat penting sebagai awal dari keterampilan-keterampilan lainnya. Pemelajar BIPA di UPT Bahasa Universitas Sebelas Maret Surakarta mengalami kesulitan dalam keterampilan menyimak dikarenakan terbatasnya perangkat pembelajaran. Penelitian ini bertujuan untuk mendeskripsikan pola pemakaian media pembelajaran keterampilan menyimak dalam pembelajaran BIPA (Bahasa Indonesia bagi Penutur Asing) di UPT Bahasa Universitas Sebelas Maret. Metode penelitian menggunakan metode studi kasus dan teknik pengumpulan data menggunakan observasi, wawancara, dan analisis dokumen. Teknik pengampilan sampel dengan menggunakan Hasil penelitian menunjukkan bahwa pemakaian media pembelajaran keterampilan menyimak dalam pembelajaran bahasa Indonesia bagi penutur asing di UPT Bahasa Universitas Sebelas Maret dilakukan dengan dua pola yaitu pemakaian media di dalam kelas dan di luar kelas. Media pembelajaran di luar kelas dibagi lagi menjadi media pembelajaran perorangan, media pembelajaran kelompok, dan media pembelajaran massal.Kata kunci: BIPA, media pembelajaran, keterampilan menyimak.